ANALISIS PERBEDAAN KESEHATAN DASAR DAN HYGIENE PERORANGAN PADA BALITA TERHADAP STATUS GIZI - Habir, Dahniar; Tosepu, Ramadhan; Asriati, Asriati (NHM PRESS, 2021)
Generally, malnutrition is a public health problem involving multi- disciplinary and must always be controlled, especially for people living in developing countries. The implementation of the Nutrition program at the Masaloka Raya Public Health Center is running well, systematically, and sustainably. However, the results of the program have not eliminated the malnutrition rate. The purpose of this study was to determine differences in nutritional intake, basic health care, individual hygiene in under-fives with poor nutritional status, and normal nutritional status in the Working Area of Masaloka Raya Public Health Center, Bombana Regency in 2021. The research design to identify the relationship between each variables, and the research design is a case-control study using the Nonparametric Mann Witney U Test. The results showed there were differences in nutritional intake foods containing energy, carbohydrates, protein, fat, and personal hygiene and basic service health on the nutritional status of children under five, (P.Value < 0.05), The dependent variable is predicted to support the improvement of nutritional status. This also explains that the reduced intake of these six factors is the cause of malnutrition